Enhancing mathematics preservice teachers’ learning achievement and research instrument development skills using a learning activity package - Poonputta, Apantee (International Journal of Innovative Research and Scientific Studies, 2025)
The purposes of the study aimed to investigate the effects of a learning activity package on mathematics preservice teachers’ learning achievement in research on mathematics teaching and their research instrument development skills. Utilizing a one-group pretest-posttest design, the sample included 25 third-year mathematics major students selected through random group sampling. The instruments used were a set of learning activity packages, a learning achievement test (multiple-choice), and a research instrument development skills form (rubric scoring). Data were analyzed using dependent samples t-test and one-sample t-test with a predetermined criterion of 75%. Results indicate significant improvements in pretest-posttest learning achievement and research instrument development skills, corroborating previous findings on learning activity package efficacy in teacher education.